Highly Accurate Scheme for the Cauchy Problem of the Generalized Burgers-Huxley Equation - Machado, J. A. Tenreiro (2017)
In this paper, a weighted algorithm, based on the reduced differential transform method, is introduced. The new approach is adopted in the approximate analytical solution of the Cauchy problem for the Burgers-Huxley equation. The proposed scheme considers the initial and boundary conditions simultaneously for obtaining a solution of the equation. Several examples are discussed demonstrating the performance of the algorithm.